A Historical Narrative on Algerian- British Collaborations: The Reign of Elizabeth II (1952 -2022) - TRIF ,Attallah; SAYAF ,Aissa; SEDDIKI ,Mohamed (Faculty of Letters and Foreign Languages Department of English, 2023)
This study explores British-Algerian collaborations during the reign of Queen Elizabeth II, particularly the scope and significance of political, economic, and cultural relations between the two nations. The concern of this work is to emphasize the importance of these ties, from Algerian political, economic and cultural contexts. The study additionally aims at identifying prospects and suggesting solutions to overcome potential obstacles for a fruitful partnership. This study employs a multidisciplinary approach, highlighting political ties, economics, and cultural accounts to understand the bilateral relationship between the United Kingdom and Algeria. It is therefore imperative to review a series of historical events and incidents, if not all forms of collaborations that range from energy cooperation and trading activities to cultural affairs and foreign policies. This would for sure help measure to what extent these ties are building both nations